2018
DOI: 10.1177/0892020617748151
|View full text |Cite
|
Sign up to set email alerts
|

Researching reciprocal leadership

Abstract: This article looks at the potential of using an online self-completing inventory that measures leadership consciousness awareness. The Consciousness Quotient inventory (CQ-i) has been developed to encourage leaders to be more conscious of their ability to be accountable and responsible for their leadership practice. The CQ-i as a method for researching leadership is piloted here between a university academic and a primary headteacher in the context of a school–university partnership. Pilot outcomes reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Leadership practice characterization is founded around a leadership style that questions established norms and motivates a collective vision by empowering people to take action, providing guidance on the necessary course to be pursued, and fostering a sense of organizational unity. In accordance with the viewpoint presented by Poultney and Fordham [6] on reciprocal leadership, this characterization supports the notion of transcending the asymmetrical and dichotomous perspective that exists between a leader and their followers. The implementation of creative changes within an organizational setting is indicative of leadership as a strategic approach.…”
supporting
confidence: 86%
“…Leadership practice characterization is founded around a leadership style that questions established norms and motivates a collective vision by empowering people to take action, providing guidance on the necessary course to be pursued, and fostering a sense of organizational unity. In accordance with the viewpoint presented by Poultney and Fordham [6] on reciprocal leadership, this characterization supports the notion of transcending the asymmetrical and dichotomous perspective that exists between a leader and their followers. The implementation of creative changes within an organizational setting is indicative of leadership as a strategic approach.…”
supporting
confidence: 86%
“…Although some exploratory studies revealed a possible predictive and incremental value of the CQ-i, related to various variables, e.g., executive functioning, academic achievements, yoga practices, pro-environmental behaviors, etc. (Brazdau and Mihai, 2011;Jones, 2012;Chauhan et al, 2013;Ahuja, 2014;Tuazon, 2014;Ahuja and Sharma, 2015;Poultney and Fordham, 2018) this was not our primary research purpose. Other studies using the CQ-i in various contexts provided additional data for questionnaire properties, and possible cross-cultural predictive validity (Raundeley and Kumari, 2016;Sharma et al, 2016;Sattar and Saaed, 2019).…”
Section: Cq-i Usability For Educational and Research Studiesmentioning
confidence: 99%
“…Regarding leadership theory, previous literature identified two types of behavioural orientations. Task-oriented leaders are resolute, determined, and own a work style with clearly defined priorities and agenda (Poultney & Fordham, 2018). Task-oriented leaders have clear objectives, established procedures, issues, distinct goals, and implements a compensation structure (Raudeliūnienė & Kordab, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%